2021
DOI: 10.1002/marc.202000759
|View full text |Cite
|
Sign up to set email alerts
|

Photoresponsive Vesicles Enabling Sequential Release of Nitric Oxide (NO) and Gentamicin for Efficient Biofilm Eradication

Abstract: The development of new antibacterial agents that can efficiently eradicate biofilms is of crucial importance to combat persistent and chronic bacterial infections. Herein, the fabrication of photoresponsive vesicles capable of the sequential release of nitric oxide (NO) and gentamicin sulfate (GS) is reported, which can not only efficiently disperse Pseudomonas aeruginosa (P. aeruginosa) PAO1 biofilm but also kill the planktonic bacteria. Well‐defined amphiphilic diblockcopolymers of poly(ethylene oxide)‐b‐pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Recently, we have successfully synthesized NO-releasing diblock copolymers based on photoresponsive N -nitrosamine moieties. , These NO-releasing diblock copolymers self-assembled into vesicles in an aqueous solution without premature NO leakage. However, phototriggered NO release was achieved under ultraviolet (UV) or visible light irradiation, showing potential applications in corneal wound healing and biofilm dispersal.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we have successfully synthesized NO-releasing diblock copolymers based on photoresponsive N -nitrosamine moieties. , These NO-releasing diblock copolymers self-assembled into vesicles in an aqueous solution without premature NO leakage. However, phototriggered NO release was achieved under ultraviolet (UV) or visible light irradiation, showing potential applications in corneal wound healing and biofilm dispersal.…”
Section: Results and Discussionmentioning
confidence: 99%
“…We found that the micellar nanoparticles were relatively stable in an aqueous solution, and the sizes of micellar nanoparticles showed negligible changes and no macroscopic precipitates were observed within at least one week, as monitored by DLS (Figure S6). Moreover, our previous results suggested that PNO diblock copolymers had a CMC value of ∼32 mg/L, which self-assembled into vesicular nanoparticles in an aqueous solution …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nguyen et al attached a NO-releasing moiety to gentamicin within a polymeric nanoparticle for simultaneous release of both compounds and observed synergistic effects against P. aeruginosa [54]. In addition, Duan et al designed photoreceptive of NO-releasing amphiphiles that can self-assemble into vesicles and incorporate the water-soluble gentamicin antibiotic within the vesicle, enabling sequential release of NO and gentamicin upon photoirradiation [55].…”
Section: Combinations Of No and Antibiotic Treatmentsmentioning
confidence: 99%
“…Simultaneous release of NO and DOX or gentamicin has also been realized by rational molecular design. [29,30] The outcomes indicate an increased antimicrobial property and synergistic effects on antitumor by controlled and simultaneous release of signaling molecules and antibiotics or antitumor agents. However, the combined donor for CO and FA has never been attempted.…”
Section: Introductionmentioning
confidence: 99%